ANALISIS HUKUM PERSAINGAN USAHA DI INDONESIA DALAM UNDANG-UNDANG NOMOR 5 TAHUN 2019 - Tarmizi Tarmizi (Jurnal Real Riset, 2022)
In the Reformation Era, there has been a fundamental change in the field of economic and business law, which is characterized among others by the birth of Law No. 5 of 1999 on the Prohibition of Monopoly Practices and Unfair Business Competition. In the law has been regulated a number of prohibitions on monopoly practices and or other unhealthy business competition, in the hopes of providing guarantees of legal certainty and equal protection to every business actor or group of business actors in trying. The provisions of the Law are actually good enough in regulating the provisions of competition law in Indonesia, but the regulation tends to still have a dimension of physical trade. In this case, Law No. 5 of 1999 does not yet have specific arrangements related to e-commerce. Furthermore, in addition to facing the potential for anti-competitive practices, the enforcement of competition law in the field of e-commerce also still faces other challenges such as with regard to the issue of the adoption of the principle of extraterritoriality in Law No. 5 of 2019.Keywords: Law, Competition, Enactment